Hypersensitivity pneumonitis associated with home mold exposure: A retrospective cohort analysis - Traci N. Adams; Carrie A. Redlich; Craig S. Glazer; Mridu Gulati (PLoS ONE, 2025)
Background Home mold exposure is a commonly overlooked cause of hypersensitivity pneumonitis. This is in part due to the limited literature supporting the association as well as the lack of exposure characterization available in reported cases. Notably, climate change, extreme weather patterns and frequent flooding continue to create conditions that promote home mold growth. As remediation has the potential to improve outcomes, clinicians need to remain vigilant in searching for and identifying potential mold exposure in suspected HP patients. The purpose of this study is to describe a large retrospective cohort of patients with home mold associated HP. Methods HP patients were identified retrospectively from our single center interstitial lung disease (ILD) database between 2011–2019. Patients with a moderate, high, or definite confidence diagnosis of HP were included. The presence of residential mold exposure was confirmed by medical chart review by a pulmonologist trained in exposure assessment. Results Home mold exposure was identified as the culprit antigen in 54 of 231 hypersensitivity pneumonitis patients. An invasive procedure (bronchoalveolar lavage, transbronchial biopsy, and/or surgical lung biopsy) was performed to confirm the diagnosis of HP in 85.7% of the cohort. Home mold was principally caused by chronic and/or recurring water intrusion. The most common locations of mold within the home included the bathroom, bedroom, and air conditioning unit. Transplant free survival was 97.7 months, which did not differ from the 50 HP patients in our cohort with HP associated with a mold exposure outside the home or patients in our cohort with HP associated with avian antigen exposure. Of the 41 patients who removed the exposure, 5 (12.2%) had a > 10% improvement in FVC, including 4 with fibrotic HP. Conclusion Our study is the largest to report an association between HP and home mold exposure and is the first report from the region of north Texas. As climate change continues to disrupt weather patterns causing storms and flooding in certain areas, clinicians should remain alert to the presence of mold and its potential contribution to development of HP.